ANALYSIS OF HEAVY METALS IN WATER AND FISH CIRRHINA MRIGALA OF RIVER GODAVARI, AT NATHSAGAR DAM IN MAHARASHTRA, INDIA - M. J. SHAIKH (The Bioscan, 2013)
The concentrations of heavy metals (Cd, Cr, Pb, Ni and Zn) in sample water and organs (muscle, gills and liver) of fish Cirrhina mrigala of river Godavari, at Nathsagar Dam in Maharashtra were analyzed. There was an appreciable decrease in metal concentrations in sample water from site I to site II. The heavy metal concentrations in sample water was in the order Ni>Pb>Cd>Zn>Cr. The concentration of Nickel was 7.53 53µg/L and that of Lead was 6.2653µg/L. Accumulation of heavy metals in the organs of fish Cirrhina mrigala was found in the order gills>muscle>liver. In the gills, lead was found maximum (3.83 µg/g dry weight), whereas chromium was minimum (0.68µg/g dry weight). In the muscles, the values of lead was 2.59µg/g, comparatively chromium was 0.64µg/g. In the liver, lead, cadmium and nickel were more concentrated compared to zinc and chromium. The concentration of heavy metals accumulated in gills and liver was found in the order Pb>Cd>Ni>Zn>Cr and in the muscles, it was found in the order Pb>Cd>Ni>Cr>Zn. In this study fish gills and muscles shows highest tendency to accumulate both lead and cadmium, while accumulation of metals is less in liver. As the fish Cirrhina mrigala is largely consumed by people, it is essential to make awareness about water pollution and effects of heavy metals on human body.